Influence of calcium carbonate on polyamide 12 regarding melting, formability and crystallization properties. (1st May 2019) - Ippolito, Fabio; Rentsch, Samuel; Hübner, Gunter; Claypole, Timothy; Gane, Patrick
Abstract: Controlling and adjusting the thermal properties of a compound to improve the additive manufacturing process of a polymer matrix through selective laser sintering is of key importance to achieve an optimized final part density as well as hardness. In the past, the purpose of adding mineral fillers to polymers was primarily one of cost reduction. Today, however, fillers are more often used to fulfil a functional role, such as improved thermal or mechanical properties of the polymer composite [1 ]. In this study, the influence of calcium carbonate as a mineral filler particle on the thermal properties in compression-molded polyamide 12 was investigated. The particle size distribution and the filler amount within the polyamide 12 matrix were varied. The melt viscosity at 190 °C, the melting speed, melting and crystallization point as well as crystallization time at 170 and 172 °C were analyzed. A relationship between these properties and the implementation of a specific amount of calcium carbonate with a certain particle size distribution was observed. The study concludes, that the thermal and flow properties of a polyamide 12 matrix can potentially be manipulated to improve a laser thermal sintering process insofar as the layer melt can be optimized as well as the crystallization process speeded up.